2012
DOI: 10.1055/s-0032-1322618
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Repair of Mycotic Aneurysm of the Descending Thoracic Aorta: Diagnostic and Therapeutic Dilemmas—Two Case Reports with 1-Year Follow-Up

Abstract: A mycotic aneurysm of the thoracic aorta is a rare diagnosis with high mortality. We present two cases of endovascular reconstruction of mycotic descending thoracic aorta. Specific or nonspecific bacterial or other infectious agent in serial samples of blood, urine, cerebrospinal fluid, and pleural puncture was not detected in the first case, but we found in sputum sample Mycobacterium tuberculosis in the second patient. We empirically began by administering broad-spectrum intravenous antibiotics in the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…To prevent infection, the omentum or a muscle flap is used to cover the infected field. The mortality for open mycotic aortic aneurysm repair is almost 40% [1,5,6]. As shown by Sörelius et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent infection, the omentum or a muscle flap is used to cover the infected field. The mortality for open mycotic aortic aneurysm repair is almost 40% [1,5,6]. As shown by Sörelius et al.…”
Section: Discussionmentioning
confidence: 99%
“…A lower mortality rate is associated with endovascular treatment of mycotic aortic aneurysms supported with antibiotics from the beginning of treatment, though a stent graft is put in an infected filed [6,9]. Although there is no consensus on the optimal duration of antibiotic therapy, parenteral antibiotics are commonly given for 2–8 weeks after surgery [2].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the English literature from 2008 to today revealed 28 more cases (Table 1) [3], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], specifically 18 men and 10 women with a mean age of 44.64 ± 18.16 years (range 16–84). 7 patients had a history of pulmonary tuberculosis and had previously received anti-tuberculosis medication.…”
Section: Discussionmentioning
confidence: 99%